Microclimate, yield and must composition of Syrah grapevine cultivated under plastic cover - Pedro Júnior, Mário José; Hernandes, José Luiz; Santos, Antonio Odair; Lino, Antonio Carlos Loureiro (Revista de Ciências Agroveterinárias, 2019)
The characterization of vineyard microclimate, plant variables and must physicochemical properties of the ’Syrah’ wine grape was done for plants cultivated with and without waterproof plastic cover (“ráfia”). The grapevines were trained in Y-shaped trellis and cultivated during the winter growing season in the grape growing region of Louveira-SP, Brazil. During the grape maturation period, measurements of solar radiation and air temperature were taken at cluster height. In the harvest, the plant variables (number of branches, number of clusters, bunch weight and yield) and must physicochemical characteristics (soluble solids content, total titratable acidity, tartaric acid, anthocyanin, total polyphenols and tannins) were determined. Maximum temperature values were higher under plastic cover when compared to the open sky condition while solar radiation values were higher for the open sky condition. Yield and total soluble solids content values were higher for vines grown under plastic cover. No influence of the use of plastic cover was found for the levels of anthocyanin, total polyphenols and tannin of berries.